Foreign experience of innovative capacity management - Utegenova, Zh.S.; Suslov, V.I. (BUKETOV BUSINESS REVIEW, 2017)
The development of science and high efficiency of R&D carried out in conjunction with a number of other factors, economic and political nature led to the unprecedented development of the productive forces in the developed countries of the world. The growing role of innovation places new demands on the choice of the most effective mechanisms for the use and evaluation of innovativecapacity, management of innovative activity of the enterprise. In order to adequately assess the current situation and the choice of perspective directions of innovative development of the enаterprise is necessary to conduct a systematic evaluation of the available innovativecapacity. So the innovative development is a major factor in improving the competitiveness of the national economy. In turn, the purpose of innovation development - achieving a quality of economic development based on improving the competitiveness of the national economy. In the article the approaches to the definition of the enterprise innovationalcapacity are given, also it presents the global innovation index for five years.